Analysis of 'linking farmers to markets' for carrots, cabbages and snow peas in Aileu Vila, Maubisse and Hatubuilico, Timor Leste - Correia, Vicente de Paulo (Curtin University, 2014)
This study analysed models of linking farmers to markets in Timor Leste. The objective is to analyse the supply chain for horticultural produce with the view of studying mechanisms for LF2M. Mixed method approach was used in the study. The study found that by strengthening supply chain linkages, LF2M led to increases in production and quality of horticultural products. Success factors include good management and communication, external support, partners’ commitment, innovation and specialization.